Travelling Paradigms: Marxism, Poststructuralism and the Uses of Theory - McGuckin, Eric (Anthropologica, 2022)
As tourism is extending commoditization into every corner of the globe, poststructuralist approaches to the anthropology of tourism tend to focus on consumption, the ironies of cultural hybridization, and the instability or "virtuality" of identity and authenticity. While useful in the representation of highly particularized intersections of discourse and desiring bodies, poststructuralist discourses may tend to dematerialize political and economic processes with significant impacts on communities subjected to the tourist gaze. Using the author's fieldwork on the tourism industry in Dharamsala, India for context, this paper argues that by reemphasizing a focus on material production and class relations, and by transcending discourses of authenticity and virtuality through Marxist conceptions of alienation, an "engaged anthropology" of tourism can more usefully link the ironies of postmodern consumption with the inequalities that continue to be structured through capitalist production.